IMRT for head and neck cancer: reducing xerostomia and dysphagia - Wang, XiaoShen; Eisbruch, Avraham (Journal of radiation research, 2016)
Dysphagia and xerostomia are the main sequellae of chemoradiotherapy for head and neck cancer, and the main factors in reducing long-term patient quality of life. IMRT uses advanced technology to focus the high radiation doses on the targets and avoid irradiation of non-involved tissues. The decisions about sparing organs and tissues whose damage causes xerostomia and dysphagia depends on the evidence for dose–response relationships for the organs causing these sequellae. This paper discusses the evidence for the contribution of radiotherapy to xerostomia via damage of the major salivary glands (parotid and submandibular) and minor salivary glands within the oral cavity, and the contribution of radiotherapy-related effect on important swallowing structures causing dysphagia. Recommendations for dose limits to these organs, based on measurements of xerostomia and dysphagia following radiotherapy, are provided here.